Aktualisasi Kepemimpinan Sekolah Berbasis Nilai-Nilai Aswaja di SDIT Mutiara Palabuhanratu Kabupaten Sukabumi - Tita Rustina; Ahmad Jaelani Latif; Indra Maulana; Halimatussadiah Halimatussadiah; Kania Dewi Sulistia; Husen Husen; Resya Restiawati; Imam Asrofi (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This study aims to describe and analyze in depth the actualization of school leadership based on the values of Ahlussunnah Wal Jama'ah (Aswaja) at SDIT Mutiara Palabuhanratu, Sukabumi Regency. The research method uses a descriptive qualitative approach with a case study design. Data was collected through interviews, observations, and documentation studies of various parties involved in school management. The results of the study show that school leadership integrates Aswaja values, namely tawassuth (moderate), tawazun (balanced), i'tidal (firm/straight), and tasamuh (tolerant), in policy making, curriculum management, and character development of students. The actualization of these values has an impact on the creation of a harmonious, inclusive, and oriented learning environment for the development of moderate Islamic character. An important point found is the integration of Aswaja values in the school's visions and missions, student discipline, and religious programs such as morning dhikr and dawn lectures. These programs support the formation of righteous, intelligent, and outstanding students, while strengthening the school's identity as an educational institution based on moderate Islamic values. This research confirms that Aswaja-based leadership not only serves as a normative guideline, but also as a practical strategy in building a school culture that is sustainable and relevant to the needs of the community.